Effect of microbe as fertilizer on the growth of Acacia mangium on the sand sterile in green house (Biodiversitas Journal of Biological Diversity, 2016)
An experiment on the effect of microbe as fertilizer on the growth of Acacia mangium on the sand sterile in greenhouse. The aim of the experiment the effect and potency of the microbe as fertilizer to increase the growth of A. mangium. The experiment was carried out in green house condition in Microbiology division, Research Center for Biology-LIPI with sterile sand medium. The Rhizobium strains used of: 1.Bio 199R, 2. Bio 203R, 3. Bio 205R, 4 Bio 238R, 5. Bio 251R, 6.Bio 7R, and 7. mixed strains (Bio 199R+Bio 203R+Bio 205R+Bio 238R+Bio 251R+Bio 7R) The controls were uninoculated withRhizobium strain and without urea fertilizer (K1), uninoculated and with urea fertilizer equal 100 kg/ha (K2). The researchdesign was Completely Randomized Design with three replications for each treatment. The plants were harvested after 70 days; the parameters of investigation were the dry weight of canopy, roots, nodules root, total plants, number of nodules and â€œsymbiotic capacityâ€. The results showed that all of experiment plant able to from nodule. Strain number of mixed strains has given the best results on the growth of A. mangium plant.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: Rhizobium strain, Acacia mangium.